2017
DOI: 10.1038/s41598-017-02892-w
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for protective quenching in antenna proteins of Photosystem II

Abstract: Photosynthesis is common in nature, converting sunlight energy into proton motive force and reducing power. The increased spectral range absorption of light exerted by pigments (i.e. chlorophylls, Chls) within Light Harvesting Complexes (LHCs) proves an important advantage under low light conditions. However, in the exposure to excess light, oxidative damages and ultimately cell death can occur. A down-regulatory mechanism, thus, has been evolved (non-photochemical quenching, NPQ). The mechanistic details of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 86 publications
2
31
0
Order By: Relevance
“…Nowadays, different LHC genes from plants, i.e., LHCII Balevičius et al 2017;Thallmair et al 2019), CP29 (Ioannidis et al 2016;Papadatos et al 2017) and PsbS Liguori et al 2019), have been simulated up to the μs timescale with atomistic resolution. Most of these works have focused in particular on characterizing how the interactions among the Chls and Cars bound to LHCs change depending on the different protein conformations sampled via MD (Liguori et al 1 3 2015; Balevičius et al 2017;López-Tarifa et al 2017;Maity et al 2019).…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, different LHC genes from plants, i.e., LHCII Balevičius et al 2017;Thallmair et al 2019), CP29 (Ioannidis et al 2016;Papadatos et al 2017) and PsbS Liguori et al 2019), have been simulated up to the μs timescale with atomistic resolution. Most of these works have focused in particular on characterizing how the interactions among the Chls and Cars bound to LHCs change depending on the different protein conformations sampled via MD (Liguori et al 1 3 2015; Balevičius et al 2017;López-Tarifa et al 2017;Maity et al 2019).…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 99%
“…The protonation pattern was chosen to model either acidic or neutral conditions in the thylakoid lumen and was kept fixed during the whole simulation. As a result of protonation of luminal residues, a conformational change was detected at the level of helix D in both LHCII and CP29 and such change was found to be able to modify the energetics of a selected Chl dimer (Ioannidis et al 2016;Papadatos et al 2017). Because from in vitro as well as in vivo results, no spectral differences are expected to be induced directly by pH in CP29 (Crimi et al 2001) and LHCII (Tokutsu and Minagawa 2013;Dinc et al 2016;Liguori et al 2016), it could be possible that the actual pKa of CP29 and LHCII residues is too low to match the protonation pattern assigned in these simulations.…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 99%
“…Energy quenching in LHCII is activated under high light, for instance during the operation of the xanthophyll cycle, which induces the pH-dependent de-epoxydation of violaxanthin into zeaxanthin and implicates xanthophyll molecules present in Lhcb complexes. However the precise mechanism involved in the quencher formation remains to be determined and so far the binding of zeaxanthin has been proposed to favor a conformational change of LHCII by inducing new chlorophyll-chlorophyll or xanthophyll-chlorophyll interactions that would open an energy dissipation channel [62][63][64]. This mechanism however seems to be common to multiple, if not all Lhcb sequences, as the pigment binding properties seem shared between complexes.…”
Section: Sequence Conservation and Divergence Clues For Regulation Mmentioning
confidence: 99%
“…Still using classical MD, Croce and coworkers suggested that NPQ in LHCII is probably connected to some conformational changes in the system structure [134]. Finally, Papadatos et al used MD trajectories to asses the role of pH variation and of the xanthophyll cycle on the NPQ of LHCII [135,136]. To the best of our knowledge, NPQ in cyanobacteria, instead, has never been studied with atomistic computational techniques.…”
Section: From the Lh Function To Its Photoregulationmentioning
confidence: 99%